Analysis of The Effect Of Exchange Rate, Leverage, And Liquidity On Financial Performance With Firm Age As A Control Variable - Zakiyya, Salma Roihana; Edward, Mohammad Yunies (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the influence of exchange rate, leverage, and liquidity on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2023, with firm age as a control variable. Methodology: Using a quantitative approach, the sample was selected through purposive sampling, resulting in 113 manufacturing firms. The variables observed include return on assets (ROA), debt ratio (DR), current ratio (CR), exchange rate, and firm age. Data were analyzed using panel regression with a fixed effect model based on the Hausman test. Results: The results indicate that leverage has a significant negative effect on financial performance, while liquidity and exchange rate have no significant effect. Firm age as a control variable does not significantly affect ROA. Findings: The study highlights the importance of managing debt levels to maintain profitability and supports previous literature on capital structure theory. Novelty: This research incorporates firm age as a control variable and uses a decade-long data panel from Indonesian manufacturing companies. Originality: This study contributes a comprehensive view of macro and micro financial determinants of firm performance in a developing economy context. Conclusion: Companies must manage leverage carefully to avoid profitability decline. High liquidity or long firm age does not guarantee better performance. Type of Paper: Research article